EFFECTS OF THE EXPERIMENTAL INFECTION IN CHICKENS, Gallus gallus, BY INFECTIVE LARVAE OF Libyostrongylus douglassii AND L. dentatus, NEMATODES FROM OSTRICHES, Struthio camelus - Gallo, Samira Salim Mello; Ederli, Nicole Brand; Morte, Murilo de Oliveira Bôa; de Oliveira, Francisco Carlos Rodrigues (Brazilian Journal of Veterinary Medicine, 2010)
ABSTRACT. Gallo S.S.M., Ederli N.B., Bôa-Morte M.O., de Oliveira F.C.R. [Effects of the experimental infection in chickens, Gallus gallus by infective larvae of Libyostrongylus douglassii and L. dentatus, nematodes from ostriches, Struthio camelus].Efeitos da infecção experimental em frangos, Gallus gallus, com larvas infectantes de Libyostrongylus douglassii e L. dentatus, nematóides de avestruzes, Struthio camelus. Revista Brasileira de Medicina Veterinária, 32(1): 26-32, 2010. Laboratório de Sanidade Animal, Hospital Veterinário, Centro de Ciências e Tecnologias Agropecuárias, Universidade Estadual do Norte Fluminense Darcy Ribeiro, Av. Alberto Lamego, 2.000, Parque Califórnia, Campos dos Goytacazes, RJ 28013-602, Brasil. Email: foliveira@uenf.br With the objective to investigate the possible effects of the infection by Libyostrongylus spp., 48 one-day-old chickens was divided into three groups (inoculated, immunocompromised and control) with 16 birds each. The infected groups received an inoculum consisted of 4.500 and 500 infective larvae of L. douglassii and L. dentatus, respectively. The immunocompromised group received also a dose of 0.2 mg of dexamethasone. Were measured daily the consumption of fodder and water, and on the 3rd, 7th, 14th, 24th, 38th and 52nd days after inoculation, birds in each group were slaughtered and had measured separately the live weights, the carcass weights and organs weights. Samples were also collected for histopathology. The data were statistically analyzed using the Tukey test. The infective larvae of the genus Libyostrongylus were able to cause damage in chickens in the initial development phase in an attempt to establish the infection. However, these parasites are unable to complete their life cycles in these animals.